Structural interpretation of 2D seismic reflection data of the Khabour Formation in the Upper West Euphrates, western Iraq - Abdullah, Ali M.; Al-Rahim, Ali M. (Iraqi Journal of Science, 2022)
The seismic reflection method has a primary role in petroleum exploration. This research is a structural interpretation study of the 2D seismic reflection survey carried out in the Upper West Euphrates (Khan Al-Baghdadi area), which is located in the western part of Iraq, Al-Anbar governorate. The two objectives of this research are to interpret Base Akkas/Top Khabour reflector and to define potential hydrocarbon traps in the surveyed area. Based on the synthetic seismogram of Akk_3 well near the study area, the Akkas/Top Khabour reflector was identified on the seismic section. Also, the Silurian Akkas Hot_shale reflector was identified and followed up, which represents the source and seal rocks of the Paleozoic petroleum system in the Western Desert of Iraq. Time, velocity, depth, and isopach maps were drawn for Base Akkas/Top Khabour reflector and showed the presence of two anticline structures trending east-west and located on the west side of the study area. The first is termed as (A), represented by Tulul structure, and the second is termed as (B). The maps show the increase in time toward the eastern side of the study area. The general slope of the reflectors is toward the southeast of the study area, while the increase of the thickness of the Formation is gradual to the southwest as well as the northwest of the study area. The study area was affected by three transversal faults. Generally, the faults have northeast-southwest trends. The Ordovician Khabour sands are the primary reservoir in the study area. They are interpreted to be present throughout Akkas Field as gas/condensate accumulation located 100 km to the west of the study area.